New legal forms of companies at the present stage: a comparative legal analysis - Tsarova, Liudmila V. (Journal of the Belarusian State University. Law, 2022)
The law of business partnerships and companies has traditionally been characterised by a fairly high rate of change, which is logical given the correlation between this area of law and the development of economic relations. At the same time, changes in the type diversity of companies through the creation of new organisational forms are quite rare and are usually perceived as an extraordinary innovation, characterised as a reform and attracting special attention of doctrine and practice. The article provides an overview of new organisational forms of partnerships and societies creation in Belarus, Germany and Poland over the past 30 years, identifying the aims of such reforms and the motivations of the concerned legislators to implement them. While recognising that new company forms are created in the historically unique economic, social and political environment of each state, the author concludes that the current stage of national corporate law reforms associated with the creation of new forms of partnerships and companies is focused on providing maximum flexibility in the regulation of small and medium-sized businesses in a competitive legal framework. When introducing new organisational forms, the rules on the existing organisational forms play a systemic role and are applied subsidiarily on matters not regulated by special rules.
Keywords: comparative company law; organisational form of legal entity; business company; business partnership